Plasticity in Vulnerability to Cavitation of Pinus canariensis Occurs Only at the Driest End of an Aridity Gradient - López, Rosana; Cano, Francisco J.; Choat, Brendan; Cochard, Hervé; Gil, Luis (Frontiers in Plant Science, 2016)
Water availability has been considered one of the crucial drivers of species distribution. However, the increasing of temperatures and more frequent water shortages could overcome the ability of long-lived species to cope with rapidly changing conditions. Growth and survival of natural populations adapted to a given site, transferred and tested in other environments as part of provenance trials, can be interpreted as a simulation of ambient changes at the original location. We compare the intraspecific variation and the relative contribution of plasticity to adaptation of key functional traits related to drought resistance: vulnerability to cavitation, efficiency of the xylem to conduct water and biomass allocation. We use six populations of Canary Island pine growing in three provenance trials (wet, dry and xeric). We found that the variability for hydraulic traits was largely due to phenotypic plasticity, whereas genetic variation was limited and almost restricted to hydraulic safety traits and survival. Trees responded to an increase in climate dryness by lowering growth, and increasing leaf-specific hydraulic conductivity by means of increasing the Huber value. Vulnerability to cavitation only showed a plastic response in the driest provenance trial located in the ecological limit of the species. This trait was more tightly correlated with annual precipitation, drought length and temperature oscillation at the origin of the populations than hydraulic efficiency or the Huber value. Vulnerability to cavitation was directly related to survival in the dry and the xeric provenance trials, illustrating its importance in determining drought resistance. In a new climatic scenario where more frequent and intense droughts are predicted, the magnitude of extreme events together with the fact that plasticity of cavitation resistance is only shown in the very dry limit of the species could hamper the capacity to adapt and buffer against environmental changes of some populations growing in dry locations.